We Meet in Madness - Lanave, Isabella (Revista do Colóquio, 2025)
Art as a form of personal transformation; a visual essay referring to the work of the artist, who has been photographing her mother, a neurodiverse woman, for years. The essay proposes the creation of another imaginary for what madness would be stigmatized by society. A loving look at mental and structural suffering.